A comparative analysis on the programming format of Arangkada and Sikat ka Iloilo. - Escalona, Regine Marie Granada
Hesperidin is a flavonoid found in citrus fruits. The peel and membranous parts of these fruits have the highest hesperidin concentrations. Studies have shown that hesperidin has antioxidant, anti-diabetic/lipid-modulating, anti-inflammatory effects and antimicrobial properties. The main objective of this study is to isolate and purify hesperidin from Suha peelings and to determine its gastrointestinal motility effect and antimicrobial activity., Crude hesperidin was isolated and purified from the peelings of a locally available citrus plant Suha (Citrus maxima). The isoalte was then characterized using phytochemical tests, thin layer chromatography (TLC) ananlysis and Fourier-Transform Infrared (FT-IR) Spectrometry. The isolate gave positive results for the phytochemical tests, indicating the presence of flavonoid in the isolate. The TLC analysis indicated Rf values for H1 (0.31+-0.03) and H2 (0.33+-0.02) close to that of the hesperidin standard (0.33). FT-IR analysis showed the bands of the isoalte matches the structure of hesperidin (61 percent match). Results from bnoth TLC and FT-IR analysis suggest that flavonoids structurally similar to hesperidin were not separated from hesperidin during the isolation process.